Positive psychological capacities: the mystery ingredient in successful service recoveries?. Issue 7 (8th October 2018) - Azab, Carol; Clark, Terry; Jarvis, Cheryl Burke
Abstract : Purpose: This paper aims to explore the influence of frontline employees' (FLEs') positive psychological capacities (PPCs) (optimism, hope, resilience and self-efficacy) on service recovery. Design/methodology/approach: A model of FLE PPCs is tested using two studies: a field study (Nretail = 205; Nrestaurant = 160) and between-subject experimental design (Neducation = 206) in three service settings. Findings: Results show that positive emotions mediate the relationship between PPCs and problem-solving adaptability, and that authenticity of positive emotions moderates the relationship between positive emotions and interactional justice. Surprisingly, problem-solving adaptability positively influences perceptions of distributive justice and interactional justice. A small interaction effect between positive emotions and problem-solving adaptability also was found. Research limitations/implications: The dependent variable (problem-solving adaptability) was measured using an open-ended question evaluated by objective, independent raters rather than a self-reported structured metric, to minimize social desirability bias. Practical implications: Given that the customer complaints to the Better Business Bureau in 2016 were close to one million, most of them occurring in the service sector, service firms need continuous research into improving service recovery. This study argues that firms can improve FLEs' problem-solving adaptability behavior by training existing FLEs to strengthen PPCs, hiring FLEs that have strong PPCs and fostering positive emotions. Originality/value: This is the first study that examines the effect of PPCs on service recovery outcomes. By incorporating PPCs as antecedents of positive emotions, this paper explains how FLEs can offer a better recovery rather than dictating what they ought to display and say. An explanation of how FLE PPCs influence customer outcomes via the broaden-and-build theory of positive emotions and emotion contagion theory is offered, highlighting a novel path/relationship between FLE positive emotions and problem-solving abilities, and extending emotion contagion to service recovery.